Relasi Etnisitas dan Integrasi Sosial: Studi Suku Bugis dan Suku Jawa di Lamarukung Kecamatan Tellu Siattinge Kabupaten Bone - Mrs. Hastuti; Supriadi Torro (Rayhan Intermedia, 2023)
This research aims to determine (1) The pattern of relationship between the ethnicity of the Bugis Tribe Community and the Javanese Tribe Community in Lamurukung Village, Tellu Siattinge District, Bone Regency. This type of research is descriptive qualitative, determining informants using a purposive sampling technique with predetermined criteria for informants, namely, village heads, Bugis community leaders and Javanese community leaders in Lamurukung Village, Tellu Siattinge District, Bone Regency for at least 5 years. With data collection techniques carried out by means of Observation, Interviews and Documentation. And data analysis is carried out by reducing data, presenting data, and drawing conclusions. The results of this research show: (1) In Lamurukung Village there are 4 patterns of relationships carried out by the Bugis Tribe Community and the Javanese Tribe Community, namely: a) The pattern of social relationships between the Bugis Tribe Community and the Javanese Community in carrying out life together b) The pattern of social relationships The Bugis Tribe Community with the Javanese Community in the system of cultural and religious values c) The pattern of social relations between the Bugis Tribe Community and the Javanese Tribe Community in the marriage system d) The pattern of social relations between the Bugis Tribe Community and the Javanese Community in the livelihood system